2004
DOI: 10.1002/chem.200305232
|View full text |Cite
|
Sign up to set email alerts
|

Solid‐Phase Synthesis of 89 Polyamine‐Based Cationic Lipids for DNA Delivery to Mammalian Cells

Abstract: The ability of non-viral gene delivery systems to overcome extracellular and intracellular barriers is a critical issue for future clinical applications of gene therapy. In recent years much effort has been focused on the development of a variety of DNA carriers, and cationic liposomes have become the most common non-viral gene delivery system. Solid-phase synthesis was used to produce three libraries of polyamine-based cationic lipids with diverse hydrophobic tails. These were characterised, and structure-act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 42 publications
0
35
0
Order By: Relevance
“…The polar head group generally has one or more cationic head consisting of guanidinium, [10][11][12] amine (primary, secondary, tertiary, or quaternary), [13][14][15] or pyridinium moieties. [16][17][18][19] The linker is usually a biodegradable chemical bond (ester, amide, or carbamoyl) [10][11][12][13][14][15] or a nondegradable ether bond. [20,21] The hydrophobic tail represents a nonpolar hydrocarbon that can be grouped into two categories: hydrocarbon and steroid (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The polar head group generally has one or more cationic head consisting of guanidinium, [10][11][12] amine (primary, secondary, tertiary, or quaternary), [13][14][15] or pyridinium moieties. [16][17][18][19] The linker is usually a biodegradable chemical bond (ester, amide, or carbamoyl) [10][11][12][13][14][15] or a nondegradable ether bond. [20,21] The hydrophobic tail represents a nonpolar hydrocarbon that can be grouped into two categories: hydrocarbon and steroid (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%
“…[23,24] Cationic lipids with cholic acid and other analogues as hydrophobic tails have also been reported. [11] Herein, a library of 180 cationic lipids with the various combinations of hydrocarbon chains and cholesterol as hydrophobic tails were synthesized and evaluated for their transfection efficiency (Scheme 2). Combinatorial solidphase synthesis was used to prepare these lipids because this allows the highly efficient production and purification of diverse libraries of compounds in the search for new therapeuAbstract: The ability of a nonviral gene delivery system to overcome extra-and intracellular barriers is a critical issue for the future clinical applications of gene therapy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…31 Futaki et al found that oligoarginines of 4-16 residues were found to be able to transfect cells, and N-terminal stearylation of the peptides increases the transfection efficiency by approximately 100 times to reach the same order of magnitude as that of Lipofectamine.…”
Section: Discussionmentioning
confidence: 99%
“…Guanidine and its salts are important intermediates for organic synthesis and medicine; they have also been proposed for making cationic lipids for gene delivery. Yingyongnarongkul et al (Yingyongnarongkul et al, 2004) studied a library of aminoglycerol-diamine conjugatebased cationic lipids with urea linkage between varying length of diamines and hydrophobic chains, and found two compounds with bis-guanidinium and one tail had transfection activity superior to that of the commercial lipid transfection reagent effective and merit further investigation. In addition, several cationic lipids containing guanidine (Floch et al, 2000), amidine (Lensink et al, 2009), or cyclic guanidine in the head group have been studied.…”
Section: Headgroup Domainmentioning
confidence: 99%